2006
DOI: 10.1139/y06-017
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium deficiency augments myocardial response to reactive oxygen species

Abstract: Magnesium (Mg) deficiency and oxidative stress are independently implicated in the etiopathogenesis of various cardiovascular disorders. This study was undertaken to examine the hypothesis that Mg deficiency augments the myocardial response to oxidative stress. Electrically stimulated rat papillary muscle was used for recording the contractile variation. Biochemical variables of energy metabolism (adenosine triphosphate (ATP) and creatine phosphate) and markers of tissue injury (lactate dehydrogenase (LDH) rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…It has been reported that Mg deficiency enhanced the debilitating effects of ischemic injury [51] and stress sensitivity, which probably resulted in cardiovascular damage and arrhythmias [52]. It can also induce elevation of intracellular Ca 2+ concentrations, alterations in membrane permeability and transport processes in cardiac cells [50].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that Mg deficiency enhanced the debilitating effects of ischemic injury [51] and stress sensitivity, which probably resulted in cardiovascular damage and arrhythmias [52]. It can also induce elevation of intracellular Ca 2+ concentrations, alterations in membrane permeability and transport processes in cardiac cells [50].…”
Section: Discussionmentioning
confidence: 99%
“…To study whether the increased lipid peroxidation and ROS were caused by altered antioxidant activities, the activities of superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT) were detected. These enzymes are important to plants for eliminating ROS ( Alscher et al., 2002 ; Manju and Nair, 2006 ). Under mock and pathogen infection conditions, SOD, POD, and CAT activities were much higher in OE plants than in WT plants ( Figures S2 A and S2B).…”
Section: Resultsmentioning
confidence: 99%
“…The COC meat pellets reputably had the highest absolute concentration of total unsaturated fatty acid among all treatments. This is an important finding because a slight increase in serum HDL-Cholesterol levels was assumed to be synonymous with a lower risk for cardiovascular disease in humans [7].…”
Section: Treatment Weeksmentioning
confidence: 96%
“…In fact, magnesium deficiency was known to cause hypercholesterolemia, hypertriglyceridaemia and dyslipoproteinaemia characterized by an increase of LDL-Cholesterol as well as decrease of HDL-Cholesterol in rats [7]. Calcium was known to modulate lipid metabolism in experimental animals by promoting fecal excretion of saturated fatty acid [8].…”
Section: Introductionmentioning
confidence: 99%